2022
DOI: 10.1371/journal.pone.0268737
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and psychosocial support for the war-wounded: A retrospective cohort study from the Democratic Republic of Congo, Mali and Nigeria

Abstract: Background For more than 150 years, war surgery has been at the heart of the humanitarian assistance offered by the International Committee of the Red Cross (ICRC) in conflict zones around the world. Mental health and psychosocial support (MHPSS) is increasingly recognized as an integral part of the medical care offered to this highly vulnerable group of patients. This study seeks to identify patient characteristics associated with high distress prior to MHPSS and predictors of improvement following it. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Regarding concurrent validity, this study presents new results about the relationship between domestic violence as assessed by DVQ and different variables of interest. A direct positive relationship was validated between depression symptoms and DVQ scores, congruent with prior findings, thus providing support for the internal validity of the DVQ (Andersen et al, 2022;Calvete et al, 2007;Sharma et al, 2021). Second, mental wellbeing presented significant negative correlations with DVQ scores (Mootz et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Regarding concurrent validity, this study presents new results about the relationship between domestic violence as assessed by DVQ and different variables of interest. A direct positive relationship was validated between depression symptoms and DVQ scores, congruent with prior findings, thus providing support for the internal validity of the DVQ (Andersen et al, 2022;Calvete et al, 2007;Sharma et al, 2021). Second, mental wellbeing presented significant negative correlations with DVQ scores (Mootz et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…To address the mental health treatment gap in LMICs, then, there is a need to develop psychosocial interventions that are culturally appropriate and embedded in local knowledge, values and practices 56 . Although most medical and psychological interventions have been developed and evaluated in high-income countries, this review found positive effects for psycho-social interventions such as group therapy, music therapy, family support, and socio-economic projects 18 , 36 , 37 . This matches previous research in humanitarian settings, which supports the efficacy of psychosocial interventions for adults with common mental disorders 57 , and therapy for reducing suicidal ideation 58 .…”
Section: Discussionmentioning
confidence: 93%
“…Thirty-one studies (64%) were conducted in the Eastern region of the DRC, a region devastated by war and sexual violence 6 . Among the remaining 19 studies, two were cross-national looking at the association between key factors 18 , 19 , four looked at the service provision at the national level 20 22 , eleven were conducted in the capital city Kinshasa, one was conducted in Vanga health zone in Central-West region, and one study was conducted in Equateur in the North-West region, and one study conducted in the southeast. All studies were published between 2005 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations